2010
DOI: 10.1021/ol902890j
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of a Fluorescent Artemisinin Derivative to Endoplasmic Reticulum

Abstract: A cytotoxic artemisinin derivative conjugated with a fluorescent dansyl moiety was synthesized and its subcellular localization in Hep3B cells was examined. Comparison of the localization signals of the fluorescent artemisinin derivative with organelle specific dyes revealed that endoplasmic reticulum (ER) is the main site of its accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 43 publications
1
41
0
1
Order By: Relevance
“…8,12,5052 For example, depending on the experimental model, some drug derivatives concentrate in the endoplasmic reticulum while others localize in the mitochondrion. 51 It seems a consensus, based on the structure-function relationship of this class of compounds, 52 that artemisinins do not bind specific targets. Instead, the modification of protein function by artesunate, as might to be the case with Keap1, probably involves protein thiol residues and alkylation reactions.…”
Section: Discussionmentioning
confidence: 99%
“…8,12,5052 For example, depending on the experimental model, some drug derivatives concentrate in the endoplasmic reticulum while others localize in the mitochondrion. 51 It seems a consensus, based on the structure-function relationship of this class of compounds, 52 that artemisinins do not bind specific targets. Instead, the modification of protein function by artesunate, as might to be the case with Keap1, probably involves protein thiol residues and alkylation reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a fluorescent artemisinin derivative ( 5 ), which showed around ten-fold more potent cytotoxicity toward the human hepatoma HepG2 cells than ART ( 1 ), was synthesized (Scheme 3 ). The subcellular localization of 5 in the human hepatoma Hep3B cells was investigated, which indicated that endoplasmic reticulum (ER) rather than mitochondria is the major locating site of 5 (Scheme 3 ) [49]. This provides an important clue for the future characterization of the molecular target of ART and its analogues for their antitumor activity.…”
Section: Characterization Of Artemisinin: From An Antimalarial Drumentioning
confidence: 99%
“…In fact, thapsigargin lacks the endoperoxide moiety and only generates discrete ROS levels. Nevertheless the ER appears to be a relevant site for artemisinin action as in HepG2 cells a fluorescent derivative has been shown to preferentially accumulate in this cell compartment [60]. …”
Section: Antitumor Mechanism Of Action Of Artemisininmentioning
confidence: 99%